2021
DOI: 10.1002/mds.28583
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐Ethnic Fine‐Mapping of the Major Histocompatibility Complex Region Linked to Parkinson's Disease

Abstract: A BS TRACT: Background: Despite evidence for the role of human leukocyte antigen (HLA) in the genetic predisposition to Parkinson's disease (PD), the complex haplotype structure and highly polymorphic feature of the major histocompatibility complex (MHC) region has hampered a unified insight on the genetic risk of PD. In addition, a majority of the reports focused on Europeans, lacking evidence on other populations. Objectives: The aim of this study is to elucidate the genetic features of the MHC region associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…We also performed analyses restricted to a single peptide (Tyrosine 39, Y39) that induces T cell responses in PD patients 11 and was previously used for binding affinity predictions. 2…”
Section: Smoking Initiation: Two-sample Mendelian Randomizationmentioning
confidence: 99%
“…We also performed analyses restricted to a single peptide (Tyrosine 39, Y39) that induces T cell responses in PD patients 11 and was previously used for binding affinity predictions. 2…”
Section: Smoking Initiation: Two-sample Mendelian Randomizationmentioning
confidence: 99%
“…Although it might be challenging to perform a detailed fine-mapping, such as haplotype analysis, reliable conditional analysis, and additional adjustment of covariates, DISH would play a sufficient role in obtaining meaningful inferences. We recently conducted trans-ethnic fine-mapping for Parkinson's disease (PD) by integrating GWAS summary statistics from different studies to detect functionally plausible risk-associated HLA variants [7].…”
Section: Hla Imputation For Gwas Summary Statisticsmentioning
confidence: 99%
“…Not confined to so-called autoimmune diseases, MHC fine-mapping studies have successfully identified the risk HLA variants of different diseases, such as infectious diseases [75,76], malignant tumors [77,78], and neurological diseases [7,79]. These studies could expand our knowledge of the involvement of autoimmunity in the progression of such diseases.…”
Section: Findings Obtained From Fine-mapping Of the Mhc Regionmentioning
confidence: 99%
See 2 more Smart Citations